Ice Risks Management Digitalization within North Sea Route Exploitation in Polar Night - Tatiana V. VEKSHINA; Valery M. ABRAMOV; Yaroslav A. PETROV; Vyacheslav G. BURLOV; Mikhail B. SHILIN; Igor A. SIKAREV; Ekaterina M. KORINETS; Evgeniy A. BAIKOV; Eugene P. ISTOMIN; Oleg I. SHEVCHUK (Communications of International Proceedings, 2021)
Presented digitalization results for ice risks management within North Sea Route exploitation in polar night under climate change and COVID-19 pandemic. Used risk management approach, situational analysis, web technologies and methods of building databases in distributed networks. As research result, it is proposed to use active remote sensing data. As important research result, it was proposed to use designed digital modular tool that combines heterogeneous resources in distributed networks. Demonstrated examples for 2021t year. The presented in the paper research results have significant scientific novelty and can be useful for different players in arctic marine logistics. Platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for data exchange and preliminary discussion during the research.
Keywords: Ice Risks Management; North Sea Route; Polar Night; Decision Support; Climate Change